Pengembangan Modul Ajar Al-Qur’an Hadist Berbasis Exe Learning di MTs Hidayatul Muhajirin Palangka Raya - Rahmad Ramadhan; Noorazmah Hidayati; Muzakki (La-Tahzan: Jurnal Pendidikan Islam, 2025)
The teaching of Al-Qur’an Hadith at MTs Hidayatul Muhajirin Palangka Raya faces challenges in delivering normative content such as “Understanding the Position and Function of the Qur’an and Hadith in Islam,” which tends to be abstract and conventionally taught, resulting in low student engagement. To address this, this study developed a digital teaching module based on eXe Learning using the 4D development model (Define, Design, Develop, Disseminate), aiming to produce an interactive, pedagogically and technically valid learning medium responsive to students’ needs. Expert validation showed significant improvement from “Good” (67.74% content expert; 77.78% media expert) to “Very Good” (98.39% content expert; 92.11% media expert) after revision. Field trials with 7th-grade students (small group: 10 students; large group: 30 students) yielded highly positive responses, with satisfaction levels of 89% and 90%, respectively, categorized as “Very Satisfied/Very Effective” according to Sugiyono (2017). In conclusion, the eXe Learning-based module is proven to be valid, engaging, and effective in enhancing students’ motivation and comprehension of normative content, serving as an innovative solution for transforming Islamic religious education in the digital era.